Kajian hazard analysis critical control point pada proses produksi air minum dalam kemasan: Study hazard analysis critical control point on the bottled drinking water production process - Alamsyah, Riski Saputra; Mardiana; Tubagus, Robi; Aprilianto, Kevin (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2024)
Bottled drinking water is raw water that has been processed and packaged properly so that it is safe for direct consumption. One of the concepts and strategies for ensuring food safety and quality that is considered more effective and has been recognized for its reliability internationally is the Hazard Analysis Critical Control Point (HACCP) food safety management system. This research aims to determine how to implement Hazard Analysis Critical Control Point (HACCP) in the demineralized water production process at CV. Tirta Guna Mandiri. The method used in the research is the descriptive method which describes the objects in the research. The data collection technique used is by conducting library studies, interviews, Focus Group Discussions (FGD), and documentation. The research results show that CV. Tirta Guna Mandiri has implemented 12 steps to implement HACCP which include establishing a HACCP team, product description, intended use, flow diagram verification, hazard analysis, determining Critical Control Points (CCP), determining critical limits, establishing a monitoring system, determining corrective actions, verification procedures, and establishing documentation